UNITED STATES’ SOFT DIPLOMACY TOWARDS INDONESIA THROUGH AMERICAN INSTITUTE FOR INDONESIAN STUDIES (AIFIS) - Lisda Rud Auri Manurung; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Soft diplomacy has been used by United States to achieve its national interests. Among many ways, United States uses soft diplomacy through American Institute for Indonesian Studies (AIFIS) towards Indonesia. AIFIS is a consortium of universities and colleges in the United States interested in furthering the development of Indonesian studies. Therefore, this research was conducted to explain how the United States uses AIFIS as a means of soft diplomacy to increase mutual understanding between United States and Indonesia.This research uses a pluralism perspective in which non-state actors are important actors in international relations and nation-states as level of analysis. Theory applied for this research was the multi-track diplomacy theory, which asserts that diplomacy can be practiced by involving community elements including educational institutions. This research method uses a qualitative method.  This research shows that the United States uses AIFIS as a soft diplomacy instrument towards Indonesia by facilitating researchers and scholars of the United States and Indonesia through the awarding of scholarships. AIFIS also cooperates with universities and academic institutions in Indonesia, cooperates with the government, and organizes academic events. Moreover, AIFIS provides resource, library and language-learning center. Overall, AIFIS has a commitment to increase mutual understanding between Indonesia and United States through interactions in science. Keywords: Soft Diplomacy, AIFIS, Educational Institution, Multi-track Diplomacy, Researchers, Mutual Understanding.